2017
DOI: 10.1007/s12630-017-0885-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic medical record interventions and recurrent perioperative antibiotic administration: a before-and-after study

Abstract: These inexpensive nonintrusive interventions to the EMR provided modest lasting improvements in proper administration of repeated doses of cefazolin. The fact that only approximately 70% compliance was reached highlights the difficulty in addressing this deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Each year, over 700 000 Americans suffer a deep vein thrombosis (DVT) and pulmonary embolism (PE), the most common manifestations of VTE (1). In the U.S. VTE claims 100 000 lives annually and costs the healthcare system $13.5 billion to treat . Roughly 25% of VTE's occur during hospital stays, yet, approximately 60‐70% can be prevented with appropriate prophylaxis .…”
Section: Eras and Vte‐prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, over 700 000 Americans suffer a deep vein thrombosis (DVT) and pulmonary embolism (PE), the most common manifestations of VTE (1). In the U.S. VTE claims 100 000 lives annually and costs the healthcare system $13.5 billion to treat . Roughly 25% of VTE's occur during hospital stays, yet, approximately 60‐70% can be prevented with appropriate prophylaxis .…”
Section: Eras and Vte‐prophylaxismentioning
confidence: 99%
“…In the U.S. VTE claims 100 000 lives annually and costs the healthcare system $13.5 billion to treat. [42][43][44] Roughly 25% of VTE's occur during hospital stays, 43 yet, approximately 60-70% can be prevented with appropriate prophylaxis. 44 In recognition of this opportunity to improve patient outcomes, professional organizations like the American Academy of Chest Physicians (AACP), have published comprehensive guidelines on the proper use of both pharmacological and mechanical VTE prophylaxis.…”
Section: Eras and Vte-prophylaxismentioning
confidence: 99%
“…Reminders to respond to these events can easily be integrated into the EMR, either in the form of a time bar for repeatedly administered drugs, such as the intervention evaluated by Hincker et al, 1 or in the form of an ''if event X is present then send a recall to do Y'' loop. These reminders are all the more important as the events that they prompt can occur during intraoperative moments of high cognitive workload (e.g., during patient hemorrhage).…”
Section: Preventing Medical Errorsmentioning
confidence: 99%
“…1 In their before-and-after cohort analysis, they showed that this was achieved through the use of a simple bar on the EMR monitor that displayed continuously from the start of the initial antibiotic dosing and ended 15 min before subsequent doses were indicated. Such a straightforward adjustment to the EMR management software can have a direct effect on a practitioner's adherence to practice guidelines and could ultimately impact patient safety.…”
mentioning
confidence: 99%
“…This low percentage approximates the dismal values published by other institutions that have audited their intraoperative antibiotic redosing rates. 10,12,13 Therefore, anesthesia and pharmacy providers at the University of Iowa initiated a quality improvement project to increase compliance with published PPA intraoperative redosing recommendations for surgical procedures lasting more than 4 hours.…”
mentioning
confidence: 99%